Early Diagnosis of Latent Tuberculosis Reactivation due to Drug Interaction between Cobicistat and Intranasal Fluticasone - Roberto Pineda-Reyes; Alena Klochko (Case Reports in Infectious Diseases)
Background. Single-tablet antiretroviral therapy is currently the first-line choice for the treatment of HIV infection. Some therapeutic regimens contain the CYP3A4 inhibitor cobicistat, which can interact with drugs undergoing hepatic first-pass metabolism, leading to unintended adverse effects. Case Presentation. A 41-year-old man presented to the HIV clinic following a visit to the Emergency Department. His CD4+ count was 1,271 cells/μL, and viral load was undetectable in the previous month. The patient was on an antiretroviral therapy regimen containing cobicistat. He reported using a self-initiated over-the-counter fluticasone nasal spray for at least 2 weeks prior. He had a history of positive tuberculin skin test and a negative chest X-ray within the past year. He denied cough and was in no respiratory distress. A chest CT scan revealed a new thick-walled cavitary nodule in the right upper lobe. A CT-guided biopsy of the lesion yielded Mycobacterium tuberculosis. Conclusions. HIV-infected individuals have higher risk for tuberculosis reactivation regardless of their CD4+ count. Fluticasone’s hepatic metabolism is bypassed in the presence of CYP3A4 inhibitors, which increases its systemic bioavailability and the risk for impaired immunity. The goal of this report is to increase awareness among physicians about the potential adverse outcomes from the interaction of these drugs.